Analisis Pendapatan Usahatani Pepaya California (Carica Papaya L) di Kecamatan Hinai Kabupaten Langkat - Tri Gustiawansyah; Siti Sabrina Salqaura (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
The agricultural sector plays a vital role in supporting Indonesia's economy, particularly in food provision and increasing rural household income. One of the promising horticultural commodities is California papaya (Carica papaya L.), known for its high productivity and short harvesting cycle. This crop is favored by farmers due to its stable market demand. However, to ensure the financial feasibility of this farming enterprise, a comprehensive financial analysis is necessary. This study aims to analyze the revenue, production costs, income, and financial feasibility of California papaya farming in Hinai Subdistrict, Langkat Regency. The research employed a descriptive quantitative method through a survey approach, with a purposive sample of 34 farmers. Data were analyzed using a farm income analysis approach, including the calculation of fixed costs, variable costs, total revenue, net income, and the Revenue/Cost (R/C) ratio. The results showed that the total production cost was IDR 590.734.000, while the total revenue reached IDR 1.970.685.000. The net income obtained by farmers amounted to IDR 1.379.951.000, with an average income of IDR 40.586.794 per farmer. The R/C ratio was calculated at 3.33, meaning that every IDR 1 spent on production costs generated IDR 3.33  in revenue. California papaya farming in Hinai Subdistrict is financially feasible, provides significant profit, and has strong potential to be further developed as a primary income source for horticultural farmers.